Sentence Elements in Terms of Role and Reference Grammar - Rejeb, Suliman I. (Humanities Journal of University of Zakho, 2019)
Kurdish sentences, like those of other languages, should be described and explained by different theories to identify the most appropriate theory for describing them. Therefore, choosing Kurdish sentences is a step to make this study different from other studies which have been carried out in this aspect. Role and Reference Grammar is one of structural and functional theories arrived at by the two scholars, Foley and Van Valin (1980) as a reaction to Transformational Grammar. This type of grammar deals with the syntactic, semantic and pragmatic aspects as three different elements and at the same time it connects the syntactic and logical elements with information element relevant to the sentence. This study deals with identifying sentence elements, i.e. it identifies the position of sentence elements in terms of Role and Reference Grammar. The sentences under investigation are those ones used in everyday situations and references.